PENGARUH PENGENCER KUNING TELUR AYAM DENGAN AIR KELAPA MUDA TERHADAP INTEGRITAS MEMBRAN PLASMA DAN ABNORMALITAS SPERMATOZOA DOMBA SAPUDI PENGARUH PENGENCER KUNING TELUR AYAM DENGAN AIR KELAPA MUDA TERHADAP INTEGRITAS MEMBRAN PLASMA DAN ABNORMALITAS SPERMATOZOA DOMBA SAPUDI - Cesaria, Mayrena Ayu; Estoepangestie, A.T.Soelih; Susilowati, Suherni; Hernawati, Tatik; Madyawati, Sri Pantja; Triana, Indah Norma (Ovozoa: Journal of Animal Reproduction, 2019)
This study aimed to determine the influence of mixture diluter of chicken egg yolk and young coconut water on the integrity of plasma membrane and abnormalities of Sapudi sheep spermatozoa. The experimental design used in this study was a complete random method. The data was analysed using ANOVA, and if there is a significant difference then proceed with Duncan's Multiple Range Test ( DMRT ) at significance level of 5%. Based on the result of the research, the influence of mixture diluter of chicken egg yolk and young coconut water was not significantly different ( p > 0,05 ) on the intact plasma membrane of spermatozoa on the first day until the fourth day. Interaction between treatment and storage duration had no effect on spermatozoa abnormality on the first day, second day and the fourth day. It can be concluded that mixture diluter of chicken egg yolk and young coconut water had a good effect on the plasma membrane and spermatozoa abnormalities up to the third day.